Evaluation of substrates in a hydroponic lettuce culture system in the municipality of Pasto - Guerrero, Elizabeth Marcela; Revelo, Juan Camilo; Benavides B., Orlando; Chaves J., Germán; Moncayo, Carlos Álvaro (Revista de Ciencias Agrícolas, 2014)
Horticulture is a strong economic line in Nariño; this project was done as an alternative to improve the production and quality of lettuce. The evaluation of coconut fiber and rice husks substrates for a hydroponic A-frame structure system for the production of lettuce (Lactuca sativa L.) was carried out at the International Center for Clean Production Lope, SENA Regional Nariño. A total of 200 plants were cultured in an area of 10 square meters, from which plant height, diameter, total weight, and head and root weight variables were evaluated. An unrestricted random sampling design with 5 treatments and 4 replicates was performed, where treatment 1 corresponded to 100% rice husks substrate, treatment 2 to a mixture of 70% rice husks and 30% coconut fiber, treatment 3 to a mixture of 50% of each of substrate, treatment 4 to a mixture of 70% coconut fiber and 30% rice husks, and treatment 5 to 100% coconut fiber substrate. The results showed that the treatments with a mixture of coconut fiber and rice husks were better compared to the individual substrate treatments, with the former plants showing the best physiological development in diameter, head weight, and performance. In terms of profitability, treatment 4 with 70% coconut fiber and 30% rice husks substrate mixture was the best by 12%.